Analisis Kualitas Pelayanan Terhadap Tingkat Kepuasan Konsumen(Studi Empiris Pada Rumah Sakit Universitas Sebelas Maret Surakarta) - Umbara, Desi Verania, Drs. Wiyadi, M.M., Ph.D (2017)
This study aims to analyze the effect of service quality on the level of customer satisfaction empirical study at Sebelas Maret University Hospital (UNS).This research method using research type of quantitative approach. The sample in this study were as many as 100 community respondents or patients who visited or treated at at Sebelas Maret niversity Hospital (UNS) by using convenience sampling method. Data analysis methods used were validity test, reliability test, classical assumption test and multiple linear analysis test with t test, F test, and coefficient of determination (R²). The result of t test analysis can be obtained that direct evidence (tangible) have positive and significant effect to patient satisfaction, Reliability (reliability) have a positive and significant impact on patient satisfaction, Responsiveness has a positive and significant impact on patient satisfaction, assurance (assurance) has a positive and significant effect on patient satisfaction, Attention (empathy) has a positive and significant effect on patient satisfaction of Sebelas Maret University Hospital (UNS) individually while the F test results can Obtained tangible, reliability, responsiveness, assurance, empathy together have an effect on patient satisfaction of Sebelas Maret University Hospital (UNS). Keywords: Tangible, Reliability, Responsiveness, Assurance, Empathy And Patient Satisfaction.